¿Qué nos dicen las autocorrecciones sobre la aprendibilidad y el desarrollo de la adquisición de las lenguas segundas? : las formas regulares e irregulares del pasado de los verbos del español no nativo. - Mongeon, Caroline. (University of Ottawa (Canada), 2001)
The goal of this thesis is to investigate whether and in which respect self-repairs can provide information on how non-native speakers of Spanish acquire regular and irregular past tense verb forms. According to Pinker and Prince's (1988, 1992) 'Dual Mechanism model' regular and irregular forms are not represented the same way in the speakers' mind: regular forms are computational, i.e. they respond to rule-governed mechanisms (as in look-ed, walk-ed). On the other hand, irregular forms are vocabulary items which are concatenated in the lexicon as one-piece units (as in the case of went, spoke). In this thesis we investigate whether this proposal is also valid in the case of Spanish past tense verb forms. Spanish verbs, unlike English verbs, are highly inflected and irregular forms not only have an irregular stem but they also have person, number, tense and aspect morphemes. By analysing the oral production of Spanish learners with different ages and from different learning environments, we have tried to contribute to the debate around the so-called 'Dual Mechanism' model.
Keywords: Language, Linguistics.